Structure of the Geothermal Atlas of Belarus - Dubanevich, Marharita A.; Zui, Vladimir I.; Martynova, Olga A. (Journal of the Belarusian State University. Geography and Geology, 2019)
Geothermal investigations in Belarus were started in the beginning of sixties of the past century. A considerable geothermal data were accumulated until present time on the thermal regime of the platform cover within the country – thermograms of boreholes, thermal properties of rocks, heat flow density, data on the recoverable resources of an underground heat. Results of longterm investigations are reflected in generalized form in the published Geothermal Atlas as a series of geothermal maps described by a brief accompanying text. The Geothermal Atlas was published for the first time; it includes 10 summary maps for the whole territory of the country and 16 maps additionally for the beststudied sedimentary basin of the republic, which is the Pripyat Trough. They reflect a considerable contrast of the geothermal field within the country. The heat flow catalogue for Belarus is included into the atlas. It was prepared according to the format suggested by the International Heat Flow Commission. It includes data on 497 studied boreholes. Maps of the Geothermal Atlas were compiled for following topics: maps of the temperature distribution for depths of 100; 200; 300; 400 and 500 m for the whole territory of the country. They were supplemented for these depths for the territory of the Pripyat Trough, which is best studied in geothermal respect; maps of the temperature distribution for depths of 1; 2; 3 and 4 km, as well as maps for stratigraphic thicknesses of the Pripyat Trough: surfaces of roofs of the Upper Salt, Intersalt Deposits, the Lower Salt, carboniferous and terrigenous complexes underlying the Lower Salt; maps of geothermal gradients for the depth intervals of 100 –200 and 200 –300 m for the whole territory of Belarus, the heat flow density map based on the heat flow catalogue, included into the atlas; maps of the recoverable resources of geothermal energy for depth intervals of 100 –200 and 200 –300 m, as well as for the thickness of the Devonian age overlying the Upper Saltcomplement this work.
Keywords: geothermics; temperature; heat flow; geothermal maps; geothermal atlas; geothermal resources